2018
DOI: 10.1155/2018/1435389
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Wound Dehiscence after Penetrating Keratoplasty and Lamellar Keratoplasty

Abstract: Objective To investigate the incidence, causes, occurrence time, and range of wound and outcomes of wound dehiscence in patients treated by penetrating keratoplasty (PK) or lamellar keratoplasty (LK). Methods We retrospectively reviewed medical records of keratoplasty in Shandong Eye Hospital from January 2006 to June 2017. Thirty-one eyes of 30 patients had sustained wound dehiscence (WD) after surgical treatment. The surgical type, causes, occurrence time, extent of the wound, treatment, and outcomes were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
(24 reference statements)
1
12
0
Order By: Relevance
“…In addition to the early and later advantage of stabilizing the wound on both the donor and recipient side preventing spontaneous [30,31] and maybe reducing the consequences of post-traumatic wound dehiscence [32] after keratoplasty, the CDR-ACXL technique performed prior to DALK in our experience has proven to be useful during the trephination phase, which in this case it occurs on a compacted tissue resulting more facilitated and precise.…”
Section: Corneal Cross-linking (Cxl) As Adjuvant Treatment In Dalk Surgerymentioning
confidence: 87%
See 1 more Smart Citation
“…In addition to the early and later advantage of stabilizing the wound on both the donor and recipient side preventing spontaneous [30,31] and maybe reducing the consequences of post-traumatic wound dehiscence [32] after keratoplasty, the CDR-ACXL technique performed prior to DALK in our experience has proven to be useful during the trephination phase, which in this case it occurs on a compacted tissue resulting more facilitated and precise.…”
Section: Corneal Cross-linking (Cxl) As Adjuvant Treatment In Dalk Surgerymentioning
confidence: 87%
“…A secondary effect of CXL proved by in vivo confocal microscopy is cellular apoptosis and keratocytes repopulation with deposition of new higher resistant collagen fibres and increased resistance against collagenase activity. Some authors have suggested to use CXL in the pre-treatment of corneal graft for the decellularization [29], thus preventing the rejection [30,31]. In our protocol we use the circular donor-recipient bidirectional 9 mW/5.4 J/cm 2 Accelerated CXL [27] and we named this approach proposed by Mazzotta "Circular Donor-recipient Accelerated Crosslinking" or CDR-ACXL and The innovation of our technique consists in applying for the first time a peripheral [25] or annular "doughnuts-shaped" Accelerated 9mW CXL [28] preoperatively in both the donor [23] and the recipient corneas [25] with different timing.…”
Section: Corneal Cross-linking (Cxl) As Adjuvant Treatment In Dalk Surgerymentioning
confidence: 99%
“…However, sutures may lead to the induction of irregular astigmatism, infection, neovascularization and trauma, although its incidence is relatively low. The incidence of suture-related complications ranges from 1.0% to 10.8% [29][30][31] according to the existing reports. The procedure that eliminates the need for sutures has the potential to improve the outcomes and lower the rates of postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Corneal wound healing after keratoplasty is a slow and complex phenomenon. Different studies demonstrated that corneal scar tissue at graft-host interface never regains the same tensile strength as before keratoplasty [6, 7], being decreased by 50% from a normal cornea, as described by Gassett and Dohlman [8]. The graft-host interface becomes an important point of weakness of the cornea [9].…”
Section: Discussionmentioning
confidence: 99%
“…WD incidence after PKP ranges from 0.6 to 5.8%, and the most important reason is trauma. Tseng et al [ 10 ] described a possible correlation between WD incidence and age, with older people more affected than younger although Wang et al [ 7 ] did not find a correlation with age. Rehany and Rumelt [ 11 ] reported traumatic WD to be more common in younger individuals and especially in those who had undergone keratoplasty for keratoconus.…”
Section: Discussionmentioning
confidence: 99%